PENDIRIAN UNIT PENGOLAHAN SUSU MENJADI KEFIR PADA KPS EKA PUTRA JAYA CIKERUH SUMEDANG JAWA BARAT - Sri Ndaru Arthawati; Sri Mukti Wirawati; Sri Artha Rahma Mevlanillah (FEB Universitas Sultan Ageng Tirtayasa, 2017)
Farm product is mainly consumed because it has a role in Society growth. One of dairy farm product that mainly consume is milk. The national needs of milk has been increased each year because of population increasement in Indonesia. KPS Eka Putra Jaya is one of dairy farm run in dairy cattle field in individual scale established since December 1996 and has been able to utilize this prospective opportunity. Business development study for establishment of the processing unit of milk into kefir is examined for the feasibility based on financial and non financial aspect. The result from non financial aspect reveal the business of processing unit of milk into kefir is feasible to run. While based on financial feasibility analysis, this business feasibility is adequate. This is based on the calculation result of NPV is larger than 0 in amount of Rp 374 191 826. Net B/C value is larger than 1 of 2.67. Gross B/C also more than 1 of 1.21. Time required to return the investment (Payback Period) in 2 years and 2 month. IRR result is 57.81%